Innovation in Education Service Policies in Indonesia - Tetet Cahyati; Diah Pudjiastuti (Jurnal Aktor, 2022)
This article examines the innovative policies in education service delivery in Indonesia. It explores the background and rationale behind the need for policy innovation in the education sector. The article discusses various innovative approaches and initiatives introduced by the Indonesian government to enhance the quality, accessibility, and inclusivity of education services. It analyzes the impact and challenges of these innovative policies and provides recommendations for further improvement. The article concludes by emphasizing the importance of continuous innovation and collaboration to ensure the provision of quality education services in Indonesia.